2014
DOI: 10.1093/ndt/gfu033
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study of icodextrin on the treatment of peritoneal dialysis patients during acute peritonitis

Abstract: As compared with glucose-based peritoneal dialysis solution, use of icodextrin achieved better ultrafiltration and fluid control during acute peritonitis complicating continuous ambulatory peritoneal dialysis, although we found no evidence of a worthwhile clinical benefit on peritonitis resolution. (ClinicalTrial.gov number, NCT0104446 [ClinicalTrial.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
1
9
1
3
Order By: Relevance
“…Temporary use of hypertonic exchanges and short dwell times may be needed to maintain adequate fluid removal. Temporary use of icodextrin solution may prevent fluid overload in PD patients with acute peritonitis ( 342 ). Because of rapid glucose absorption, glycemic control may worsen in diabetic patients.…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Temporary use of hypertonic exchanges and short dwell times may be needed to maintain adequate fluid removal. Temporary use of icodextrin solution may prevent fluid overload in PD patients with acute peritonitis ( 342 ). Because of rapid glucose absorption, glycemic control may worsen in diabetic patients.…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…PD patients tended to suffer from fluid overload during acute peritonitis because of ultrafiltration decline; thus, they may need more hypertonic glucose dialysate to facilitate fluid removal. Indeed, a recent clinical trial from Hong Kong demonstrated more than 30% of CAPD patients may require additional dialysate exchanges to achieve fluid balance during the course of peritonitis [27]. In this study, there were 28 (15.0%) patients who had to increase PD dose or use solution with higher glucose concentration because of acute ultrafiltration decline.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, diuretic is effective in increasing urine output. Glucose-sparing solution icodextrin shows strengths in fluid removing during acute peritonitis versus conventional glucose-based solution, and thus, it is strongly recommended [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Most trials explicitly excluded patients with acute peritonitis, but one focused specifically on such patients. 84 One study included solely patients with hypertension related to volume overload. 85 Baseline patient characteristics are detailed in Table S4.…”
Section: Trial and Patient Characteristicsmentioning
confidence: 99%